2009
DOI: 10.1038/ijo.2008.278
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a low-fat, high-protein or high-carbohydrate ad libitum diet on weight loss maintenance and metabolic risk factors

Abstract: Background: High-protein (HP) diets are often advocated for weight reduction and weight loss maintenance. Objective: The aim was to compare the effect of low-fat, high-carbohydrate (HC) and low-fat, HP ad libitum diets on weight maintenance after weight loss induced by a very low-calorie diet, and on metabolic and cardiovascular risk factors in healthy obese subjects. Design: Forty-eight subjects completed the study that consisted of an energy restriction period of 5-6 weeks followed by a weight maintenance pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
167
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(182 citation statements)
references
References 48 publications
8
167
2
5
Order By: Relevance
“…Four randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to protein on systolic and diastolic blood pressure, all of which were included in the meta-analysis (Appel et al, 2005;Leidy et al, 2007;Claessens et al, 2009;Delbridge et al, 2009). Three trials were subsequently identified in the update search (Aldrich et al, 2011;Gogebakan et al, 2011;Toscani et al, 2011) (Cardio-metabolic review, incident hypertension and blood pressure chapter p 51, 55 ; Update search table 48).…”
Section: 24mentioning
confidence: 99%
See 3 more Smart Citations
“…Four randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to protein on systolic and diastolic blood pressure, all of which were included in the meta-analysis (Appel et al, 2005;Leidy et al, 2007;Claessens et al, 2009;Delbridge et al, 2009). Three trials were subsequently identified in the update search (Aldrich et al, 2011;Gogebakan et al, 2011;Toscani et al, 2011) (Cardio-metabolic review, incident hypertension and blood pressure chapter p 51, 55 ; Update search table 48).…”
Section: 24mentioning
confidence: 99%
“…Six randomised controlled trials that presented evidence on diets differing in the proportion of carbohydrate to protein on fasting triacylglycerol concentration were included in the meta-analysis (Due et al, 2004;Appel et al, 2005;Noakes et al, 2005;Leidy et al, 2007;Claessens et al, 2009;Delbridge et al, 2009). Two trials were subsequently identified in the update search (Toscani et al, 2011;Gogebakan et al, 2011) Fasting total cholesterol 5.50.…”
Section: Fasting Triacylglycerolmentioning
confidence: 99%
See 2 more Smart Citations
“…If people increase their protein intake, they start losing weight without counting calories or controlling portions. Replacing carbohydrates with proteins can lead one on a fast track to weight loss [9,10].…”
Section: Introductionmentioning
confidence: 99%